Optimalisasi Peran Pasukan Amal Sholeh (PASKAS): Strategi Sosialisasi Gerakan Infak Beras di Kota Parepare - Zubayr, Muh; A. Nurkidam; Syam, Muh. Taufiq; Iskandar; Mutmainnah, A. Nurul (Institut Agama Islam Negeri Parepare, 2025)
Pasukan Amal Sholeh (PASKAS) is a humanitarian social movement focused on assisting the underprivileged, orphans, Quran memorizers, and those in need of support in the path of Allah (fii sabilillah), with its rice donation program being one of its main initiatives. This study aims to analyze the strategies used by PASKAS to socialize the rice donation movement, as well as to identify the supporting and inhibiting factors in its implementation. Using personal communication theory, Max Weber's social action movement theory, and dakwah bil hall, this qualitative research employs observation, interviews, and documentation methods, with data analysis techniques including data reduction, presentation, and conclusion drawing. The results show that PASKAS' socialization strategy in Parepare City has been successful, with an approach targeting institutions, schools, religious study groups (majelis taklim), and crowded places. Supporting factors include the openness of institutions to cooperate, while inhibiting factors involve the limited number of PASKAS members. The impact of this socialization is an increase in the number of foster parents joining the movement